Anthropogenic Carbon in the Nordic seas and Arctic Ocean, 1994 to 2007 - Meisingset, Anne Kari Øhman (The University of Bergen, 2019)
The increase of anthropogenic CO2 between 1994 and 2007 is quantified in the Nordic seas and Arctic Ocean with the extended multiple linear regression method (eMLR(C*)). To be able to map the increase in anthropogenic CO2 with the eMLR(C*) method in all parts of the Nordic seas and the Arctic Ocean, climatological distribution for the seven variables; temperature, salinity, alkalinity, AOU, nitrate, phosphate, and silicate, have been prepared. Anthropogenic carbon concentrations in the Nordic seas have increased by between 5.0 and 11.1 \(μ\)mol/kg between 1994 and 2007. The increase in column inventories of anthropogenic CO2 in the Nordic seas were about 15 - 25 moles/m^2, with the largest increase in the Lofoten Basin. The results for the Nordic Seas agrees in general with previous studies. However, in the Greenland Sea, the increase of anthropogenic CO2 is a bit lower than expected. This may be a result of increasing deep mixing that brings old water masses, with relatively low concentrations of anthropogenic CO2, to the upper ocean. The Arctic Ocean has the highest estimates of anthropogenic CO2, both for column inventories and individual water masses. Some parts of the Eurasian Basin have a column inventory of about 30 moles/m^2, associated with a very large increase in anthropogenic CO2 for some of the water masses. These high values are likely unrealistic and related to variability in data coverage and water mass distributions, as well as to deficiencies in the water mass definition schemes themselves. Masteroppgave i meteorologi og oseanografi GEOF399 MAMN-GEOF